2018
DOI: 10.1080/20009666.2018.1527670
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and attitudes towards safety events reporting among residents in a community health system

Abstract: Background: Resident physicians are known to be infrequent reporters of patient safety events (PSE). Previous studies assessing barriers to resident PSE reporting have not considered possible cultural barriers faced by international medical graduates (IMG). This study aimed to assess the knowledge and attitudes of residents regarding PSE and possible barriers contributing to poor resident reporting.Methods: A cross sectional survey of all house staff undergoing post-graduate residency training at two independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Given the positive effect of patient safety culture, we, therefore, proposed that:Hypothesis One: patient safety culture relates positively to nurses’ near-miss reporting intention.Error characteristics, particularly the severity of consequences, have been reported to be a critical element affecting safety performance (Chuang et al., 2007; Homsma et al., 2009; Kodama and Kanda, 2010). A study among resident physicians showed that 58.1% of respondents were more inclined to report serious errors compared with near misses (Singal et al., 2018). Most previous studies focused on actual adverse events, making it reasonable that the greater the severity of the event, the more necessary the report.…”
Section: Introductionmentioning
confidence: 99%
“…Given the positive effect of patient safety culture, we, therefore, proposed that:Hypothesis One: patient safety culture relates positively to nurses’ near-miss reporting intention.Error characteristics, particularly the severity of consequences, have been reported to be a critical element affecting safety performance (Chuang et al., 2007; Homsma et al., 2009; Kodama and Kanda, 2010). A study among resident physicians showed that 58.1% of respondents were more inclined to report serious errors compared with near misses (Singal et al., 2018). Most previous studies focused on actual adverse events, making it reasonable that the greater the severity of the event, the more necessary the report.…”
Section: Introductionmentioning
confidence: 99%
“…That study revealed that knowledge regarding what constitutes a PSE was the major barrier limiting the reporting. Similar to other studies, secondary barriers included time and complexity of the reporting process, lack of feedback, and perceived failure to resolve the issue despite reporting [6].…”
Section: Introductionmentioning
confidence: 72%
“…It included possible barriers to reporting, expressed on a Likert scale as well as three clinical vignettes designed to assess the residents' ability to identify safety events and classify them as near miss, adverse events or sentinel events and indicate whether they were reportable or not. The questions also assessed the respondent's demographic data such as gender, speciality and current level of training and medical school background [6].…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of PCIs was classified as near miss, adverse, and sentinel events, based on previous studies [13,24,25]. A near miss is defined as a preventable event in which a situation that could cause injury to a patient occurs, but leads to no actual injury [26,27].…”
Section: Research Variables 231 Severity Of Psismentioning
confidence: 99%